The Simulation of Extremely Low Cycle Fatigue Fracture Behavior for Pipeline Steel (X70) Based on Continuum Damage Model - Bo Fang; Afei Lu; Jiewei Sun; Xiaojie Li; Tao Shen (Metals, 2023)
Natural gas transmission pipelines installed in seismic and permafrost regions are vulnerable to cyclic loads with a large strain amplitude. Under these conditions, the pipe may fail in extremely low cycles, a situation which is also known as extremely low cycle fatigue (ELCF) failure. The fracture mechanism of ELCF shows significant difference to that of low cycle fatigue, and the ELCF life usually deviates from the Coffin–Manson law. Thus, it is essential to develop an effective model to predict ELCF failure of the pipeline. In this study, a series of ELCF tests is performed on pipeline steel (X70). A damage coupled mixed hardening model is developed to simulate the fracture behaviors. Continuum damage law under monotonic load is extended to cyclic load by introducing the effective equivalent plastic strain. By assuming the cyclic softening is induced by the damage accumulation, the damage parameters are fitted directly from the peak stress in each cycle. Then, the model is input into commercial software ABAQUS with a user material subroutine to simulate the fracture behaviors of these specimens. The simulation results show good agreements with the test results both under cyclic and monotonic load, which verifies the reliability of the model.